Majlis Anjung Budi @APB50 Golden Jubilee Celebration - UiTM Shah Alam, Akademi Pengajian Bahasa (Academy of Language Studies, 2022)
Akademi Pengajian Bahasa (APB) celebrated its golden jubilee in 2022 with many successful activities. The main event in conjunction with this celebration was 'Majlis Anjung Budi @APB50' which took place at Geno Hotel, Subang Jaya on 16th December 2022. It was attended by a number of dignitaries primarily Professor Datuk Ts Dr Hajah Rodziah Mohd Janor, the Vice Chancellor of UiTM, Associate Professor Ts Dr Janudin Sardi, the Dean of Akademi Pengajian Bahasa, Associate Professor Dr Nor Fazlin Mohd Ramli, the Deputy Dean of Research and Community, Associate Professor Dr Anealka Aziz Hussin, the Deputy Dean of Academic, and the Chairpersons of APB50: Associate Professor Dr Ismie Roha Mohamed Jais and Associate Professor Dr Norhazlina Husin. Other important guests who were present that night were the former Deans of APB; Professor Dr Hj Othman bin Ismail, Professor Dr Normah Abdullah, Professor Datin Dr Hajibah Hj Osman, and Professor Dato' Dr Hazadiah Mohd Dahan, APB lecturers and alumni.